Study on the gear fatigue behavior considering the effect of residual stress based on the continuum damage approach. (October 2019) - He, Haifeng; Liu, Huaiju; Zhu, Caichao; Tang, Jinyuan
Abstract: The fatigue failures of gears have great influence on lifetime and reliabilities of mechanical transmissions. Initial residual stress (IRS) induced in the manufacturing process, together with the applied loading stress, contributes to gear fatigue behavior. Gear fatigue behavior represents a continuous damaging process during a high-cycle period. In the present work, a damage-coupled numerical model considering the effect of IRS is developed to investigate the gear fatigue performance. The deterioration of gear material, the detailed evolution of damage and the stress response during the cyclic loading process are calculated and recorded based on the continuum damage mechanics (CDM) using a user material subroutine (UMAT) in ABAQUS. Both the tooth surface contact fatigue and tooth root bending fatigue of the gear are evaluated, and the influence of IRS on stress response and damage evolution is analyzed. Results show that the risk of surface contact fatigue failure of this gear is much greater than that of the tooth bending fatigue. The initial compressive residual stress has positive effect on contact fatigue performance while the initial tensile residual stress with amplitude of 380 MPa would reduce the gear contact fatigue life by 20%. Highlights: A damage-coupled fatigue model considering the effect of initial residual stress for a gear is developed based on CDM. Both the surface contact fatigue and root bending fatigue are evaluated based on stress fields and damage rates. The influence of IRS, acting as the mean stress effect, is analyzed.